2018
DOI: 10.1161/circulationaha.117.029506
|View full text |Cite
|
Sign up to set email alerts
|

GATA6 Regulates Aortic Valve Remodeling, and Its Haploinsufficiency Leads to Right-Left Type Bicuspid Aortic Valve

Abstract: The data identify a new cellular and molecular mechanism underlying BAV. The availability of an animal model for the most frequent human BAV opens the way for the elucidation of BAV pathogenesis and the development of much needed therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 47 publications
3
80
0
1
Order By: Relevance
“…This phenotype was shown to result from a defective septation process including abnormal extracellular matrix degradation and cell death. Deletion of one allele of Gata6 from SHF‐derived cells recapitulates the phenotype observed in Gata6 heterozygous mice . Conditional inactivation of Gata6 from neural crest cells or vascular smooth muscle cells led to OFT defects (mainly PTA) and lethality by E18.5‐P2, revealing an important role for GATA6 in the formation of the OFT and the aortic arch .…”
Section: Role Of Cardiac Gata Factors In Embryonic Developmentmentioning
confidence: 55%
See 3 more Smart Citations
“…This phenotype was shown to result from a defective septation process including abnormal extracellular matrix degradation and cell death. Deletion of one allele of Gata6 from SHF‐derived cells recapitulates the phenotype observed in Gata6 heterozygous mice . Conditional inactivation of Gata6 from neural crest cells or vascular smooth muscle cells led to OFT defects (mainly PTA) and lethality by E18.5‐P2, revealing an important role for GATA6 in the formation of the OFT and the aortic arch .…”
Section: Role Of Cardiac Gata Factors In Embryonic Developmentmentioning
confidence: 55%
“…GATA6 plays an essential role in the growth of a population of cells important for the generation of the extraembryonic tissues in the developing blastocyst and Gata6 null mice die embryonically due to extraembryonic defects and problems with visceral endoderm function . Recent work has shown that Gata6 heterozygous mice have high incidence of RL‐type BAV, the most common BAV diagnosed in humans . This phenotype was shown to result from a defective septation process including abnormal extracellular matrix degradation and cell death.…”
Section: Role Of Cardiac Gata Factors In Embryonic Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The Gata6‐positive population does not originate from Shh‐positive progenitors (Mesler et al , ) and an alternative possibility is that it arises from Sox9 progenitors (Fig A). Regulation of Sox9 by Gata6 has been shown in several organs, including the pancreas (Carrasco et al , ) and cardiac valves (Gharibeh et al , ).…”
Section: Discussionmentioning
confidence: 99%